2009
DOI: 10.1371/journal.pone.0006997
|View full text |Cite
|
Sign up to set email alerts
|

High-Density Microwell Chip for Culture and Analysis of Stem Cells

Abstract: With recent findings on the role of reprogramming factors on stem cells, in vitro screening assays for studying (de)-differentiation is of great interest. We developed a miniaturized stem cell screening chip that is easily accessible and provides means of rapidly studying thousands of individual stem/progenitor cell samples, using low reagent volumes. For example, screening of 700,000 substances would take less than two days, using this platform combined with a conventional bio-imaging system. The microwell ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 45 publications
0
51
0
1
Order By: Relevance
“…The cell lines were maintained, in parallel with the chip-experiments, in 100 mm cell culture dishes (BD Falcon, BD Biosciences, San Diego, CA) and split sub-confluence using a 0.25% Trypsin/0.53 mM EDTA solution (Invitrogen). Cell seeding into the microwells were performed in a manual fashion, using a pipette as described earlier [14]. For fluorescence staining of cells, calcein AM (Molecular Probes) was applied to A-431 cells.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The cell lines were maintained, in parallel with the chip-experiments, in 100 mm cell culture dishes (BD Falcon, BD Biosciences, San Diego, CA) and split sub-confluence using a 0.25% Trypsin/0.53 mM EDTA solution (Invitrogen). Cell seeding into the microwells were performed in a manual fashion, using a pipette as described earlier [14]. For fluorescence staining of cells, calcein AM (Molecular Probes) was applied to A-431 cells.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, for future studies it will be interesting to compare the effectiveness of anatase, rutile and amorphous titania for biocompatibility and how this changes with particle size and film porosity. The titania film was then applied to microwell chips that have previously been shown to be suitable for culture and analysis of mouse embryonic, adult neural and human embryonic stem cells [14]. In the previous study, conventional coatings like poly-L-lysine, fibronectin etc were used as a first step in the daily protocol.…”
Section: Figure 3 Time Course Of Msc Growth On Glass Slides Coated Wmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past decade much has been done to miniaturize cell-based screenings by creating alternative platforms such as droplet microfluidic platforms [11][12][13][14][15] , DropArray of Curiox, SlipChip [16][17][18][19][20] , platforms based on hydrophobic-hydrophilic patterning [21][22][23] and miniaturized microplates [24][25][26][27] . Droplet microfluidics enables generation up to a billion homogeneous droplets encapsulating cells.…”
Section: Introductionmentioning
confidence: 99%
“…14 We have previously developed a microwell slide for cellular analysis, 15 which consisted of an array of (14 Â 48) microwells that could accommodate up to 672 single cells for cultivation over several weeks. The microwell slide was used to perform heterogeneity analysis on clonal expansion from single carcinoma cells, 16 culture and clonal assays of stem cells, 17 and polymerase chain reaction (PCR) amplifications and minisequencing. 18 In a previous paper, we showed that it was possible to integrate the microwell slide with microfluidic channels to facilitate liquid handling and enhance single cell analysis.…”
Section: Introductionmentioning
confidence: 99%